Causal association of lipoprotein-associated phospholipids on the risk of sepsis: a Mendelian randomization study - Zeng, Liying; Tang, Haoxuan; Chen, Jiehai; Deng, Yijian; Zhao, Yunfeng; Lei, Hang; Wan, Yufei; Pan, Ying; Deng, Yongqiang (Frontiers in Endocrinology, 2024)
Background: Many previous studies have revealed a close relationship between lipoprotein metabolism and sepsis, but their causal relationship has, until now, remained unclear.Therefore, we performed a two-sample Mendelian randomization analysis to estimate the causal relationship of lipoprotein-associated phospholipids with the risk of sepsis.A two-sample Mendelian randomization (MR) analysis was performed to investigate the causal relationship between lipoprotein-associated phospholipids and sepsis based on large-scale genome-wide association study (GWAS) summary statistics.MR analysis was performed using a variety of methods, including inverse variance weighted as the primary method, MR Egger, weighted median, simple mode, and weighted mode as complementary methods. Further sensitivity analyses were used to test the robustness of the data.After Bonferroni correction, the results of the MR analysis showed that phospholipids in medium high-density lipoprotein (HDL; ORIVW = 0.82, 95% CI 0.71-0.95, P = 0.0075), large HDL (ORIVW = 0.92, 95% CI 0.85-0.98, P = 0.0148), and very large HDL (ORMR Egger = 0.83, 95% CI 0.72-0.95, P = 0.0134) had suggestive causal relationship associations with sepsis. Sensitivity testing confirmed the accuracy of these findings. There was no clear association between other lipoprotein-associated phospholipids and sepsis risk.Our MR analysis data suggestively showed a correlation between higher levels of HDL-associated phospholipids and reduced risk of sepsis. Further studies are required to determine the underlying mechanisms behind this relationship.